Experimental tests of post-tensioned girders strengthened with prestressed CFRP composites - Staśkiewicz, Michał; Kotynia, Renata; Michels, Julien; Czaderski, Christoph; Motavalli, Masoud (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper presents a research carried out within the framework of the Polish-Swiss “Tulcoempa” project, carried out by Lodz University of Technology and EMPA Swiss Federal Laboratories for Materials Science and Technology. The main goal of the project was to perform the first field application of an innovative, anchorless flexural strengthening with use of prestressed CFRP laminates on an existing bridge in Poland. Laboratory tests were conducted to verify the efficiency of the strengthening of two real-scale, 18.4m long, post-tensioned bridge girders reconstructed at EMPA institute. Flexural strengthening was successful and resulted in an increase of the member’s load capacity by 24% and reduction of the midspan deflection by more than 60%.